2020
DOI: 10.1080/10903127.2020.1845420
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance Calls for Substance-Related Issues Before and After COVID-19

Abstract: A c c e p t e d M a n u s c r i p t Background: The United States is currently facing two epidemics: sustained morbidity and mortality from substance use and the more recent COVID-19 pandemic. We tested the hypothesis that the pandemic has disproportionately affected individuals with substance use disorder by evaluating average daily 911 ambulance calls for substance use-related issues compared with all other calls. Methods: This was a retrospective cross-sectional analysis of 911 ambulance calls before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 11 publications
4
22
0
Order By: Relevance
“…One study of EMS OOD runs in Kentucky reported a large and significant increase in runs with transportation to ED in late March–April 2020 ( Friedman et al, 2021 ), concordant with the Kentucky trends observed here. Another study in Massachusetts found a small increase in transport refusals after the statewide emergency was declared (from 5.0% to 7.5%) ( Weiner et al, 2020 ), and we find a small but measurable drop in ED encounters for suspected OOD as well. These findings suggest that the relationship between EMS opioid runs and ED encounters for suspected OOD is complex and warrants further research.…”
Section: Discussionsupporting
confidence: 54%
“…One study of EMS OOD runs in Kentucky reported a large and significant increase in runs with transportation to ED in late March–April 2020 ( Friedman et al, 2021 ), concordant with the Kentucky trends observed here. Another study in Massachusetts found a small increase in transport refusals after the statewide emergency was declared (from 5.0% to 7.5%) ( Weiner et al, 2020 ), and we find a small but measurable drop in ED encounters for suspected OOD as well. These findings suggest that the relationship between EMS opioid runs and ED encounters for suspected OOD is complex and warrants further research.…”
Section: Discussionsupporting
confidence: 54%
“…The impact was found to be greatest for those injecting image and performance enhancing drugs. All five of the studies that were set in EMS (Table 6) employed a quantitative method [38,40,44,45,55]. All were pre-and post-studies of PWUD sampled from those who had visited emergency departments or had contact with ambulance services before and after stay-at-home restriction orders, and all were conducted within the USA.…”
Section: Treatment/recovery Services (Eight Studies)mentioning
confidence: 99%
“…Three of the five studies suggested that opioid overdoses increased during the COVID-19 stay-at-home order along with increased number of visits to the emergency department for naloxone administration [38,44,55]. Similarly, two studies showed that emergency medicine calls for opioid overdose increased during this time [40,45]. Two studies reported an increase in drug overdose deaths [38,54] but only one of these was rated as 'good' in terms of methods used and in weight of evidence.…”
Section: Treatment/recovery Services (Eight Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…The EMS workforce, and care they provide to ill and injured patients outside of the emergency department, is an integral part of the overall US emergency care system. Impacts from COVID‐19 have affected EMS service call volume, 4–7 increased EMS professional fatigue, and worsened well‐being, 8,9 and slowed the education pipeline 3 . Specifically, for the EMS education pipeline, it is believed that the majority of EMS education programs experienced at least some form of temporary closure, modifications to delivery of content and program requirements, and limited or loss of access to simulated education as well as live field and clinical opportunities 3,10–13 .…”
Section: Introductionmentioning
confidence: 99%